Amphiphilic stilbene derivatives attenuate the neurotoxicity of soluble Aβ42 oligomers by controlling their interactions with cell membranes. Issue 43 (26th October 2022) - Yu, Zhengxin; Guo, Weijie; Patel, Shrey; Cho, Hong-Jun; Sun, Liang; Mirica, Liviu M.
Abstract : Amphiphilic compounds with selectivity towards soluble Aβ42 oligomers were developed. Cell imaging studies show the compounds can reduce the interactions between Aβ42 oligomers and SH-SY5Y cell membranes, both in the presence and absence of Cu. Abstract : The misfolded proteins or polypeptides commonly observed in neurodegenerative diseases, including Alzheimer's disease (AD), are promising drug targets for developing therapeutic agents. To target the amyloid-β (Aβ) peptide plaques and oligomers, the hallmarks of AD, we have developed twelve amphiphilic small molecules with different hydrophobic and hydrophilic fragments. In vitro fluorescence binding assays demonstrate that these amphiphilic compounds show high binding affinity to both Aβ plaques and oligomers, and six of them exhibit selective binding toward Aβ oligomers. These amphiphilic compounds can also label the Aβ species in the brain sections of transgenic AD mice, as shown by immunostaining with an Aβ antibody. Molecular docking studies were performed to obtain structure–affinity relationships. To our delight, four amphiphilic compounds can alleviate the Cu 2+ –Aβ induced toxicity in cell viability assays. In addition, confocal fluorescence imaging studies provide evidence that two compounds, ZY-15-MT and ZY-15-OMe, can disrupt the interactions between Aβ oligomers and human neuroblastoma SH-SY5Y cell membranes. Overall, these studies strongly suggest that developing compounds with amphiphilic properties that target Aβ oligomers and modulate the Aβ oligomer–cell membrane interactions can be an effective strategy for the development of small molecule AD therapeutics.